Does experimental seaweed cultivation affect benthic communities and shorebirds? Applications for extensive aquaculture. Issue 3 (29th January 2023) - Martínez‐Curci, Natalia S.; Fierro, Pablo; Navedo, Juan G.
Abstract: Extensive seaweed aquaculture is a growing industry expected to expand globally due to its relatively low impact and benefits in the form of ecosystem services. However, seaweeds are ecosystem engineers that may alter coastal environments by creating complex habitats on previously bare mudflats. These changes may scale up to top‐consumers, particularly migratory shorebirds, species of conservation concern that regulate trophic webs at these habitats. Understanding how habitats are transformed and how this affects different species is critical to direct ecological applications for commercial seaweed management. We experimentally assessed through a Before‐After Control‐Impact design the potential changes exerted by Gracilaria chilensis farming on bare mudflats on the abundance, biomass, and assemblage structure of benthic macroinvertebrates, and their scaled‐up effects on shorebirds' habitat use and prey consumption. As predicted, experimental cultivation of G. chilensis significantly affects different components of biodiversity that scale‐up from lower to upper trophic levels. The total biomass of benthic macroinvertebrates increased with seaweed cultivation and remained high for at least 2 months after harvest, boosted by an increase in the median size of polychaetes, particularly Nereids. Tactile‐foraging shorebirds tracked these changes at the patch level increasing their abundance and spending more time foraging at seaweed cultivated plots. These results suggest that seaweed farming has the potential to impact shorebird populations by favoring tactile‐foraging species which could lead to a competitive disadvantage to species that rely on visual cues. Therefore, the establishment of new seaweed farms in bare mudflats at key sites for shorebirds must be planned warranting habitat heterogeneity (i.e., cultivated and non‐cultivated areas) at the landscape level and based on a previous experimental approach to account for local characteristics. Fostering properly designed extensive seaweed farming over other aquaculture industries with greater negative environmental impacts would provide benefits for human well‐being and for ecosystem functions.